Characterization of the complete chloroplast genome of Scorpiothyrsus erythrotrichus (Melastomataceae), an endemic to Hainan - Hong-Xin Wang; Lang-Xing Yuan; Qing-Hui Sun; Ai-Fang Weng; Yu-Wei Nian; Wen-Shu Chen; Qi-Xuan Meng (Mitochondrial DNA. Part B. Resources, 2021)
Scorpiothyrsus erythrotrichus belongs to Melastomataceae. Here, we present its complete plastome. To our knowledge, this is the first reported complete chloroplast genome of S. erythrotrichus. The complete plastome of S. erythrotrichus is 160,731 bp in length with a typical quadripartite structure, consisting of four regions: large single-copy (LSC) region (85,483 bp), small single-copy (SSC) region (17,007 bp), and two inverted repeat regions (IRs, 26,780 bp). It contains 128 genes (79 coding genes, four rRNAs, and 30 tRNAs). The overall GC content is 36.9% and in the LSC, SSC, and IR regions are 34.70%, 30.40%, and 42.50%, respectively. Our study contributes to the molecular phylogenetic studies of Scorpiothyrsus and Melastomataceae.